2019
DOI: 10.1017/s0376892919000201
|View full text |Cite
|
Sign up to set email alerts
|

Integrating conservation and socioeconomic development: the potential of community nurseries in Mexican protected areas

Abstract: SummaryCommunity nurseries within natural protected areas (NPAs) represent an attractive option to link biodiversity conservation with socioeconomic development, yet their functioning lacks proper assessment. Here, we analyse the national context of community nurseries in Mexican NPAs and suggest a specific framework to evaluate their viability. First, we examine the impact of a major governmental funding programme on these projects. Next, we conduct a case study in a focal nursery to identify challenges faced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…For example, in a community nursery in the state of Michoacán, southeast Mexico, 11 tree species from the dry forest, from a regional species pool of ca. 155 tree species were propagated there, and 70% of plant production centered on a single species [28,32]. The knowledge of seed scarification and direct seeding falls within the topic of propagation; seven documents were related to those topics (Table S3).…”
Section: Ecological Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in a community nursery in the state of Michoacán, southeast Mexico, 11 tree species from the dry forest, from a regional species pool of ca. 155 tree species were propagated there, and 70% of plant production centered on a single species [28,32]. The knowledge of seed scarification and direct seeding falls within the topic of propagation; seven documents were related to those topics (Table S3).…”
Section: Ecological Limitationsmentioning
confidence: 99%
“…In the dry tropical zones, the peasants are small and medium-sized farmers who do not have access to credit, insurance, or savings services, and the indigenous population also suffers from racial discrimination and lack of access to markets for their products, which are usually produced in subsistence systems [61]. For example, in a community nursery in the state of Michoacán, initially, 11 tree species from the dry forest were propagated, but in addition to ecological limitations (see Ecological limitations), they also faced low local demand for the plants they propagated [32]. A review of the planning phase of restoration projects in Mexico revealed that social variables were seldom evaluated in baseline studies and the most important socioeconomic goal for restoration projects was the generation of local employment, an immediate but short-term benefit; community participation was limited to the implementation part of the projects [4].…”
Section: Social Limitationsmentioning
confidence: 99%
“…Accessibility and readiness in nurseries, or sought-after traits frequently determine which species are used rather than their function in a specific ecological process or ecosystem function (Stanturf et al 2014). In general, there is insufficient information on the traits of tropical plants, and even if there are published papers with information, local nurseries do not have many options of useful plants for agroforestry, silvopastoral, and restoration (Luna-Nieves et al 2019).…”
Section: Species Used For Restorationmentioning
confidence: 99%